Sequel of divergent sowing dates on phenological event with yield and quality of Tossa jute (Corchorus olitorius L.) seed - Debnath, MR; Rahman, MM; Islam, SN; Nandi, PN (Bangladesh Journal of Scientific and Industrial Research, 2022)
This experiment was conducted at Jute Research Sub Station, Bangladesh Jute Research Institute, Jashore to determine phenology, yield and quality of Tossa jute seed at different sowing times starting from 15 July to 1 October, 2020. Variety O-9897 was used as plant material. Randomized Complete Block Design was followed with 4x3m plot size. Line sowing was practised. The result revealed that phenology, seed yield and quality varied significantly with different sowing dates. The earliest flowering (at 42 days) was observed from the sowing on 1 October and the most delayed flowering (at 89 days) from the sowing on 15 July. Sowing from 15 August to 1 September gave the highest yield with good quality seed. Sowing on 15 August, 2020 required 150 days and sowing on 1 September, 2020 required 139 days for pod maturation. Bangladesh J. Sci. Ind. Res. 57(1), 61-66, 2022